Methods of treating skin cancer by administering PD-1 inhibitor - M. G. FERRIE; LOWY ISRAEL (2023)
The present disclosure provides methods of treating, reducing the severity of, or inhibiting the growth of cancer (e.g., skin cancer). The methods of the present disclosure comprise administering to a subject in need thereof a therapeutically effective amount of a programmed death 1 (PD-1) antagonist (e.g., an anti-PD-1 antibody). In certain embodiments, the skin cancer is skin squamous cell carcinoma or basal cell carcinoma. 本公开提供了治疗癌症(例如，皮肤癌)，降低其严重性或抑制癌症生长的方法。本公开的方法包括向需要其的受试者施用治疗有效量的程序性死亡1(PD-1)拮抗剂(例如，抗PD-1抗体)。在某些实施方案中，皮肤癌是皮肤鳞状细胞癌或基底细胞癌。